2016
DOI: 10.1111/jam.13073
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin is an effective inhibitor of quorum sensing, biofilm formation and virulence factors in Pseudomonas aeruginosa

Abstract: This is the first study to demonstrate that quercetin is an effective inhibitor of QS, biofilm formation and virulence factors in Ps. aeruginosa. Furthermore, quercetin might have potential in fighting biofilm-related infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
147
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(160 citation statements)
references
References 52 publications
(105 reference statements)
7
147
0
6
Order By: Relevance
“…Analysis of antibacterial activity. The minimal inhibitory concentrations (MICs) of L12 and various antibiotics were calculated using the broth microdilution method (12) for each type of strain, according to the guidelines of The Clinical and Laboratory Standards Institute (2015) (13). The MIC for each drug was set as the lowest concentration required to inhibit bacterial growth.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of antibacterial activity. The minimal inhibitory concentrations (MICs) of L12 and various antibiotics were calculated using the broth microdilution method (12) for each type of strain, according to the guidelines of The Clinical and Laboratory Standards Institute (2015) (13). The MIC for each drug was set as the lowest concentration required to inhibit bacterial growth.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, many other studies have addressed the ability of phenolic compounds and different plant extracts to modulate the quorum sensing system and the biofilm formation in foodborne pathogenic and spoilage bacteria. For instance, catechin [114], naringenin [115] and quercetin [116] depicted strong anti-quorum sensing property against P. aeruginosa. Additionally, flavonoid fraction of guava (Psidium guajava L.) leaves extract inhibited the quorum sensing system of C. violaceum, and the biofilm formation, pyocyanin production, proteolytic and elastolytic activities and swarming motility in P. aeruginosa PAO1 [117].…”
Section: Anti-quorum Sensing and Antibiofilm Effects Of Plant Phenolicsmentioning
confidence: 99%
“…Thus, inhibiting the motility may reduce the biofilm formation to a certain extent. The study by Ouyang et al (2016) reported the biofilm inhibition by quercetin against P. aeruginosa PAO1 strain at a concentration of 64 lg ml -1 with 20% inhibition. However, in this study, at 250 lg ml -1 concentration quercetin showed inhibition in the range of 43Á123 to 78Á72% against PAO1 and other clinical strains of P. aeruginosa (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…; Ouyang et al . ). Hence, this study investigated into its activities against key virulence factors of catheter associated P. aeruginosa strains and protective role to the host cells during infection by P. aeruginosa in vitro .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation